Ainhoa Berasaluze Correa y Josefa Fombuena Valero (coords.) Supervisión. Voces que colaboran para super(ar)visiones. Editorial: Naullibres ISBN: 978-84-19775-39-1 - Esteban Romaní, Laura (Cuadernos de Trabajo Social, 2025)
The text presented for your consideration is a review of the book Supervisión: Voces que colaboran para super(ar)visiones, published in 2024 by Ainhoa Berasaluze and Josefa Fombuena as coordinators at Nau LLibres publishing house.